First in human measurements of abscess cavity optical properties and methylene blue uptake prior to photodynamic therapy by in vivo diffuse reflectance spectroscopy - Hannan, Md Nafiz; Sharma, Ashwani K.; Baran, Timothy M. (Journal of biomedical optics, 2024)
Efficacious photodynamic therapy (PDT) of abscess cavities requires personalized treatment planning. This relies on knowledge of abscess wall optical properties, which we report for the first time in human subjects. The objective was to extract optical properties and photosensitizer concentration from spatially resolved diffuse reflectance measurements of abscess cavities prior to methylene blue (MB) PDT, as part of a phase 1 clinical trial. Diffuse reflectance spectra were collected at the abscess wall of 13 human subjects using a custom fiber-optic probe and optical spectroscopy system, before and after MB administration. A Monte Carlo lookup table was used to extract optical properties. Pre-MB abscess wall absorption coefficients at 665 nm were (0.03 to ) and (0.08 to ) post-MB. Reduced scattering coefficients at 665 nm were (4.8 to ) and (1.6 to ) for pre-MB and post-MB, respectively. Oxygen saturations were found to be (5.6% to 100%) pre-MB and (0.0001% to 76.4%) post-MB. Determined MB concentrations were (0 to ). We observed substantial inter-subject variation in both native wall optical properties and MB uptake. This underscores the importance of making these measurements for patient-specific treatment planning.